Culture and Institutions - Alesina, Alberto; Giuliano, Paola (Journal of Economic Literature, 2015)
A growing body of empirical work measuring different types of cultural traits has shown that culture matters for a variety of economic outcomes. This paper focuses on one specific aspect of the relevance of culture: its relationship to institutions. We review work with a theoretical, empirical, and historical bent to assess the presence of a two-way causal effect between culture and institutions. ( JEL D02, D72, I32, J12, Z13)